Extremely Low‐Frequency Electric Field Exposure Increases Theta Power of EEG in both Eyes‐Open and Eyes‐Closed Resting Conditions in Healthy Male Subjects. Issue 4 (24th February 2021) - Shinba, Toshikazu; Nedachi, Takaki; Harakawa, Shinji
Abstract : The effects of extremely low‐frequency (ELF) electric field (EF) exposure on brain activity remain poorly understood. This study sought to examine the acute effects of EF exposure on brain activity by analyzing electroencephalogram (EEG) basic rhythms. The heart rate variability (HRV) was also measured to evaluate autonomic activity. Using a system that enables measurement under EF exposure, occipital EEG and electrocardiogram signals were recorded in nine healthy male subjects during daytime in eyes‐open and eyes‐closed conditions, with or without EF exposure (applied voltage: 30 kV, 50 Hz for 1 min). The EEG power and frequency‐domain HRV indices were obtained by power spectrum analysis of EEG and the RR interval trend, respectively. Resulting data revealed that the theta power of EEG was significantly greater during EF exposure in eyes‐open and eyes‐closed conditions. Other EEG rhythms and HRV indices were not affected by EF exposure. These findings suggest that exposure to 50‐Hz EF for 1 min altered brain activity by increasing the theta power. © 2021 Institute of Electrical Engineers of Japan. Published by Wiley Periodicals LLC.